The Potential of Frass BSF as an Organic Fertilizer for Making Sustainable Agriculture a Reality - Susilo, Hadi; Nurmayulis, Nurmayulis; Syahbana, Mohammad Ana; Sodiq, Abdul Hasyim (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Organic fertilizers have an important role in increasing plant growth and productivity. Currently, chemical fertilizers are considered is felt to be increasingly expensive, and rare, and can cause agricultural land to become unhealthy, and the production costs of agricultural crops to become large. One of the organic fertilizers that can be used as a new choice is organic fertilizer from Frass BSF, with several advantages, namely that the raw material is organic waste, which is abundant, easy to obtain, and cheap. This research method uses literature studies from online databases by collecting all information that explains BSF frass. The research results show the nutritional content of frass, the use of BSF frass, the role of frass as an organic fertilizer in increasing growth and productivity, as well as evaluating the effectiveness and application of frass on various types of agriculture plants.